Spectral models of microwave devices with longitudinal interaction - Грицунов, А.В.; Бондаренко, И.Н.; Бородин, А.В.; Копоть, М.А.; Свидерская, Л.И. (Radiotekhnika, 2019)
An attempt is made to expand the spectral approach, implemented formerly for the M-type devices, onto devices with longitudinal interaction like one-beam floating-drift klystrons and travelling-wave tubes. The models are intended for engineering analysis and optimization of wide class of the O-type microwave devices. The general features of the spectral models and applied algorithms of the numerical experiment are described. Preliminary results of the simulations are quoted.